IMPROVING STUDENT LEARNING OUTCOMES USING POWTOON MEDIA IN THEMATIC SUBJECTS THEME OF GROWTH AND DEVELOPMENT OF LIVING CREATURES IN CLASS III STATE ELEMENTARY SCHOOL 053975 STABAT LAMA - Dalimunthe, Siti Aurel Namirah Salim; Darwis, Umar (Media Inovasi Pendidikan dan Publikasi, 2024)
The aim of this research is to determine the application of Powtoon media to improve student learning outcomes. To find out whether Powtoon media can improve student learning outcomes. In this research, researchers used the concept of action research, which is included in the scope of applied research, which combines knowledge, research and action or classroom action research (PTK). PTK is often carried out in several action cycles. The results of this research are that the use of Audio Visual Powtoon learning media can improve the Natural Sciences learning outcomes of class III students. This can be seen from the results of research in cycle I, which showed that the average student score was 72.3% with a student completion percentage of 66.7%. In cycle II, student learning outcomes increased, namely with the average student score of 76.9% with a percentage of student learning completeness of 82.2%. So it can be stated that in the second cycle the learning process is said to be complete, because classically class III students at SDN 053975 Wampu have reached more than the minimum standard of 70% completeness. In cycle III, student learning outcomes increased, namely with the average student score of 77.6% with a percentage of student learning completion of 84.4%. So it can be stated that in the third cycle the learning process is said to be complete and better than in the second cycle, because classically class III students at SDN 053975 Wampu have reached more than the minimum standard of 70% completeness.